(untitled) (American Journal of Pedagogical and Educational Research, 2025)
This article emphasizes that it is much more important to form responsibility among younger students. It becomes most relevant from the moment a child enters school. Going to school means a drastic change in the child’s entire lifestyle. It says how important responsibility is for a child to obey the rules of behavior and achieve academic results.